2020
DOI: 10.1186/s12889-020-09204-4
|View full text |Cite
|
Sign up to set email alerts
|

Every medicine is medicine; exploring inappropriate antibiotic use at the community level in rural Ghana

Abstract: Background: Inappropriate antibiotic use is an important driver of antibiotic resistance. This study sought to explore inappropriate antibiotic use and confusing antibiotics with other medicines in Ghana using ethnomethodology research approach. Methods: This was an explorative study involving 15 in-depth interviews among health professionals and private dispensers and eight focus group discussions among 55 community members. Qualitative data were coded using Nvivo 12, thematically analysed and presented as na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 18 publications
2
26
1
Order By: Relevance
“…This issue needs to be considered before other issues of demand are addressed. 31 Community members should be able to distinguish an antibiotic from other commonly sold medicines, such as painkillers or antipyretics, regardless of where they obtain the medicine. Clear labelling of antibiotics empowers community members to be conscious about use of antibiotics and enables them to put any future communication campaign about better use of antibiotics into practice.…”
Section: Discussionmentioning
confidence: 99%
“…This issue needs to be considered before other issues of demand are addressed. 31 Community members should be able to distinguish an antibiotic from other commonly sold medicines, such as painkillers or antipyretics, regardless of where they obtain the medicine. Clear labelling of antibiotics empowers community members to be conscious about use of antibiotics and enables them to put any future communication campaign about better use of antibiotics into practice.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of knowledge about antibiotics contributes to their inappropriate use [ 36 , 37 ]. In Ghana, Afari-Asiedu et al found that antibiotics were used to treat stomachache and sores on the body [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of knowledge about antibiotics contributes to their inappropriate use [ 36 , 37 ]. In Ghana, Afari-Asiedu et al found that antibiotics were used to treat stomachache and sores on the body [ 36 ]. In our study population, awareness about the risks of antibiotics was low and most participants were unfamiliar with the notion that inappropriate use of antibiotics could lead to antibacterial resistance.…”
Section: Discussionmentioning
confidence: 99%
“…It also increases the chance of ABR development [14]. Some of these antibiotics used in this manner are for indications that, in principle, do not require antibiotics [15]. Accordingly, non-prescribed antibiotic use must become the usual choice of providers and consumers for most self-limiting illnesses [16].…”
Section: Introductionmentioning
confidence: 99%